The Earliest Syriac Reception of Dionysius - Perczel, István (Modern theology, 2008)
This essay examines the earliest Syriac reception of the Corpus Dionysiacum in the first decades of the sixth century. This reception is earlier than the standard Greek reception and moves us closer, I hypothesize, to the original text and context of the CD than do the subsequent Greek edition and commentaries of John of Scythopolis. The principal texts associated with the earliest Syriac reception all betray the influence of "Origenism," which, I argue, reflects the original milieu of the author of the CD. I conclude this essay with some thoughts on how an acknowledgement of the Origenism of the CD complicates our understanding of "orthodoxy" and "heresy" during this period.